KESEIMBANGAN KEHIDUPAN DUNIA DAN AKHIRAT QS. AL-QASAS AYAT 77; (Studi Komparatif Antara Tafsir Al-Azhar Dan Tafsir Al-Misbah) - Abdul Muiz; Musyakar Ahkam (Ma'had Aly Journal of Islamic Studies, 2026)
The concept of balance between worldly life and the hereafter is one of the fundamental principles in Islamic teachings. The Qur’an does not advocate asceticism that negates worldly life, nor does it justify a purely worldly orientation that neglects the hereafter. One of the verses that explicitly emphasizes this principle is QS. Al-Qasas verse 77, which instructs human beings to seek the happiness of the hereafter without forgetting their share of worldly life, as well as to uphold goodness and avoid corruption. This verse serves as a normative foundation for building a balanced, harmonious life oriented toward the well-being of both this world and the hereafter. This study aims to examine the interpretation of QS. Al-Qasas verse 77 according to Buya Hamka in Tafsir Al-Azhar and M. Quraish Shihab in Tafsir Al-Misbah, as well as to analyze the similarities and differences between their perspectives regarding the concept of balance between worldly life and the hereafter. The research method employed is library research, using a tahlili (analytical) tafsir approach. The data are analyzed through a descriptive-comparative technique by comparing the interpretations of the two exegetes based on their social contexts, interpretative styles, and emphases on the meanings of the verse. The results of this study indicate that both Buya Hamka and M. Quraish Shihab agree that QS. Al-Qasas verse 77 emphasizes the importance of balance between spiritual orientation toward the hereafter and worldly activities. Buya Hamka highlights moral and social aspects, as well as human responsibility as Allah’s vicegerent (khalifah) on earth, by relating the verse to social realities and ethical values. Meanwhile, M. Quraish Shihab places greater emphasis on the functional and proportional balance between worldly life and the hereafter through a contextual and analytical approach. The differences between the two lie in their interpretative styles and emphases; however, both concur that balance between worldly life and the hereafter is the key to human well-being, both physically and spiritually.